Ze studiów nad elitarną kulturą ludności grodów tzw. centralnych państwa pierwszych Piastów, czyli ponownie o wczesnośredniowiecznym grzebieniu ze Stroszek pod Gieczem. Ujęcie porównawcze - Kara, Michał (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
The article presents results of a repeated analysis of an ornamental comb made from an antler, discovered in an early-medieval open settlement in Stroszki (site 1, Nekla county, Wielkopolska province) from the late 9th century or the beginning of the second half of the 10th century. The settlement was a part of the backup facilities of the stronghold in Giecz, one of several the so-called central settlements in the Piasts’ oldest state. The comb stands out for its ornaments in the form of a large fish in a net immersed in water, made by engraving the side lining which serves as the comb’s grip. It has been established that it is an exclusive piece of work of Scandinavian craftsmanship, a single specimen or one from a short series that comes from the 9th/10th centuries or the first half of the 10th century. It represents type IB-VIII-1a according to E. Cnotliwy (1973), identical with type B1:2 according to K. Ambrosiani (1981). The ornaments bear a close resemblance to the ornaments on what is considered Frisian combs from the 9th century or, possibly, the early 10th c. An iconographic analysis of the comb has led to a hypothesis that the hygienic activities that it was used for (combing dirt and insects from hair) had a concealed symbolic sense. In this case, the comb together with similar specimens ornamented by slanting checks or filled diamonds reminiscent of a fishnet, performed the function of an anti-demon instrument. The analysed comb has been attributed to the culture of the oldest state of the Piasts where it ended up most probably as a part of ceremonial exchange between the local elites and the elites of the Baltic communities, including Scandinavian ones. It is regarded that the object’s diffusion was facilitated by mental concurrence, combining the then peoples of “barbarian” Europe.